Elias and Freud on Childhood Socialisation - Nagbøl, Søren (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
This paper offers an explanation as to why it is important for process sociology to re-read Freud’s psychoanalysis and theory of culture in the light of Norbert Elias’s theory of civilisation. We need Freud’s insights into the raising of children for a process sociology that is a part of the confrontation with Freud’s individualistic theory of culture and social understanding. For process sociology, it is important to be attentive to psychoanalytical experiences that can demonstrate that human beings are (in) a process in which they grow from childhood into the Society of Individuals.